Organisation Workshop. Beyond the Workplace: Large Groups, Activity and the Shared Object - Richards, H (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
Organisation Workshop stands for a body of practice derived from the pioneering work that Clodomir de Morais did with the Brasilian Peasant Leagues starting in the early 1960s and shown to be relevant today in situations of high unemployment. Two essential ingredients are a large group and a common resource pool. The Organisation Workshop method is illuminated by Leontiev’s “objectivised activity” concept, as well as important insights from 3 generations of activity theory (CHAT). Moraisean thought and practice are shown to open up new avenues to community development and to break new ground in the social psychology of the large group. © 2017 Taylor & Francis Group, LLC.